Effect of the Addition of Shrimp Head Flour in Feed on Increasing the Color Brightness of Peacock Cichlid Fish (Aulonocara sp.). - Rita Rostika; Naufal Aria Kusuma; Irfan Zidni; Kiki Haetami (Asian Journal of Social and Humanities, 2024)
This study aims to determine the optimal dosage of shrimp head flour addition to feed to increase the color brightness of peacock cichlid strain dragon blood. This research was carried out in Adultri Village, Cijeungjing District, Ciamis Regency with a research period from March to May 2024. The research method was a complete random design (RAL) experiment with 4 treatments for the addition of shrimp head flour which included (A) 0% control, (B) 5%, (C) 10%, and (D) 15%. The study was conducted for 50 days and observations were made on the color of fish kept every 10 days with Toca Color Finder. The results showed that the addition of shrimp head flour to the feed could increase the color brightness of peacock cichlid fish with significantly different results from the control treatment but not significantly different between the treatment with the addition of shrimp head flour. The highest color increase was obtained in treatment C with the addition of shrimp head flour of 10% with an average score of 4.53 and a color improvement value of 2.2 scores and color change values. There was no significant difference between all treatments for absolute length growth (L) and absolute weight growth (W).